Language contextualization in public space in Maluku Province: A landscape linguistics study - Risman Iye; I Wayan Simpen; I Nyoman Sedeng; I Made Netra; Ikhwan M Said; Firhriyah Inda Nur Abida (Cogent Arts & Humanities, 2023)
This research aims to examine the contextual use of language in public spaces in Maluku Province, Indonesia using a linguistic landscape approach. This study is descriptive- qualitative research, which aims to describe and analyze the context of language in public spaces in Maluku Province in great detail and depth, so that it can provide an accurate overview of the language conditions in the region. To collect data, this research uses participant observation, in-depth interviews, and documentation of signboards and information scattered in the research locations in Ambon City and Buru Island. The collected data is then analyzed qualitatively using thematic analysis. This analysis includes stages of theme identification, searching for additional information, theme grouping, and data interpretation. The results show that there are many language variations used in Maluku Province, including local languages, Indonesian, English, Roman, and Arabic. The use of these languages is influenced by the place and environment in which the language is used. Additionally, research also indicates the influence of religion, culture, and media, showing that the identity of the Maluku community is greatly influenced by the language they use.